Epidemiology of adult asthma within the Hungarian population between 2009 and 2019 – A retrospective financial database analysis - B. Sánta; A. Keglevich; T. Kovács; B. Engi; A. Südi; E. Noémi; L. Tamási (Global Epidemiology)
Background: Asthma is the most common chronic obstructive respiratory disease and is a considerable burden on the patients, caregivers and healthcare providers. However, data on epidemiology, healthcare expenditures, inhalation medication usage and comorbidities are scarce on a country-wide level. Methods: A retrospective analysis was performed on the Hungarian National Health Insurance Fund's financial database. All patients who had filled at least one prescription for asthma maintenance therapy between 2009-’19 had been enrolled. Prevalence for each year was assessed, based on prescriptions filled for asthma annually. Incidence was assessed only for 2011–’19. Frequency of exacerbations and their costs were calculated. Results: Through the study period 439,977 patients filled at least one prescription for asthma maintenance therapy. The number of patients having at least one prescription in 12 months increased by 20.34 % (from 132,292 to 159,225 patients). Between 2011–’19 an average of 20,742.1 new patients used asthma maintenance medications. Between 2009 and ‘19 an average of 4308 patients were hospitalized due to asthma, on an average 5129 times. Healthcare expenditure on hospitalizations and outpatient treatment of asthmatics increased by 28.05 %. Conclusion: Through our study period a substantial increase in patient numbers and overall expenditure was seen. Number and frequency of exacerbations however decreased over the years.